Accurate Numerical Prediction of Incompressible Fluid Flow in Lid-Driven Cavities - Fudhail, Abdul Munir (Trans Tech Publications, 2012)
In this paper, we report an efficient numerical method to predict fluid flow behavior in a square and deep lid-driven cavities. The conventional continuity and momentum equations are transformed into stream-function and vorticity formulation to reduce the number of unknown spatial quantities. Numerical experiments were performed with different values of aspect ratio and Reynolds number to investigate the effect of these dimensionless parameters on the fluid flow behavior in the cavity. In the current study, we found that the dynamics and the structure of primary vortex are significantly affected by the Reynolds number and the aspect ratio of the cavity.